The Introduction of Cassava Leaf Flour in Commercial Feed on Performance of KUB Chickens - Khaira Nova; Syahrio Tantalo; Rudy Sutrisna; Agit Darmawan; Muhammad Fadhil Vias Kusuma; Etha ‘Azizah Hasiib (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The study aimed to determine the effect and the best level of using cassava leaf flour added in commercial feed on feed intake, live weight, carcass weight, giblet weight of KUB chickens at 9 weeks. The research used completely randomized design with 4 treatments and 5 replications. Every replication consisted of 4 chickens. Eighty KUB chickens were randomly allotted into 4 treatments. The treatments were commercial feed without the addition of cassava leaf flour (P0); addition of 5% cassava leaf flour (P1); addition of 10% cassava leaf flour (P2), and addition of 15% cassava leaf flour (P3) to the commercial ration BR1. Analysis of variance was carried out to determine the effect of adding cassava leaf flour in the commercial ration BR 1 on the measured variables in KUB chickens aged 9 weeks. The result showed that adding cassava leaf flour in commercial feed showed significant effect in decreasing feed intake, live weight, carcass weight, and giblet weight in KUB chickens aged 9 weeks.